Operator University Termination Of Broadcasting: Legal Analysis Of Broadcasting Consumer Law - Sufmi Dasco Ahmad (INFOKUM, 2021)
Indonesia is a country that has a very wide sovereign area consisting of islands, therefore in the current era to be able to communicate and transact there are also various media options, one of which is through the means of communication and information technology media because of its convenience, it is increasingly in demand by the public. public. The purpose of this study to determine the legal protection of consumers in the use of pay television based on the consumer protection law. To find out legal remedies against subscription television operators for unilateral termination of broadcasts against their consumers. The approach method used in this research is a normative juridical approach. To approach the problem in this research, the research specification is descriptive-analytical. Data collection techniques through library research (library research) to obtain secondary data. The data analysis used in this research is qualitative. The results of the study indicate that (1) Legal protection for consumers in unilaterally stopping broadcasts by pay television operators is not in accordance with the Consumer Protection Act, there are still many consumer rights that are violated by business actors, as contained in consumer agreements with business actors. and Article 4 of Law Number 8 of 1999 concerning Consumer Protection. (2) Legal remedies that can be taken by consumers regarding the unilateral termination of broadcasting by pay television operators, namely consumers can file a lawsuit against Astro on the basis of acts against the law as regulated in Article 1365 of the Civil Code and acts of Default as regulated in Article 1243 Civil Code, because Astro has violated consumer rights as stipulated in the Consumer Protection Act. It is recommended that consumers be able to resolve disputes with the National Consumer Protection Agency, and can be a bridge for consumer negotiations with business actors in order to get solutions to solving existing problems. It is hoped that the government's participation in issuing policies related to consumer protection will improve the function of consumer protection institutions to provide consumer education.